Negative vascular remodelling after implantation of bioabsorbable magnesium alloy stents in porcine coronary arteries: a randomised comparison with bare-metal and sirolimus-eluting stents. Issue 3 (22nd August 2008) - Maeng, M; Jensen, L O; Falk, E; Andersen, H R; Thuesen, L
Abstract : Objective: We sought to assess vascular remodelling and neointima formation after implantation of bioabsorbable magnesium alloy stents (AMS). Design: Randomised experimental study. Interventions: AMS (n = 11), sirolimus-eluting stents (Cypher; n = 11) and bare-metal stents (BMS; n = 9) were randomly implanted in 31 porcine coronary arteries (n = 11 pigs). Main outcome measures: Neointima formation was measured by histomorphometry at 90 days. Vascular remodelling defined as change in external elastic membrane area from index intervention to follow-up was assessed by serial intravascular ultrasound (IVUS). Results: By histomorphometry, lumen (median (quartiles); AMS: 1.75 mm2 (1.07–3.26), Cypher 2.52 mm2 (2.22–5.01), BMS 4.55 mm2 (3.2–7.44); p = 0.013) and external elastic membrane area (AMS: 5.56 mm2 (4.09–6.95), Cypher 7.95 mm2 (6.45–10.92), BMS 9.08 mm2 (7.85–11.63); p = 0.014) were smallest after AMS implantation. By IVUS, external elastic membrane area at follow-up was smallest (AMS: 7.5 (2.8) mm2, Cypher 9.1 (2.7) mm2, BMS 9.9 (3.1) mm2 ; p = 0.33) and change in external elastic membrane area from index intervention to follow-up (remodelling; AMS: −1.0 (3.1) mm2, Cypher 1.0 (0.8) mm2, BMS 0.9 (1.2) mm2 ; p = 0.30) was greatest in the AMS group. In a dichotomised IVUS assessment of vascular remodelling, six AMS stents were remodelled (negative remodelling: n = 5; positive remodelling: n = 1) at 90-day follow-up (AMS versus Cypher + BMS: p = 0.001). Neointima formation was smallest in the AMS group (p<0.05 for both histomorphometry and IVUS). Conclusion: Coronary implantation of absorbable magnesium stents, compared to two non-absorbable stents, was associated with the smallest lumen area at three-month follow-up because of negative vascular remodelling.